Attention switching deficit in patients of Parkinson's disease who experience freezing of gait. Issue 4 (4th July 2023) - Mandal, Moulika; Khan, Azizuddin
Abstract: Attention switching is involved in postural adjustments for gait. A deficit in attention switching was expected among patients having Parkinson's disease and experiencing freezing. There was a deficit in attention switching abilities among the patients of Parkinson's disease, having episodes of freezing of gait. The task accuracy and reaction time of the freezing group was significantly reduced compared to the non-freezing group having Parkinson's disease and healthy control group on total AST task performance, congruent and incongruent trials. The non-freezing group with Parkinson's disease was also slower than the healthy control group, but its accuracy was not affected. The results suggest that patients with freezing of gait experienced a stronger deficit in attention-switching than the non-freezing group of Parkinson's disease. This attention switching deficit among freezers may imply inappropriate allocation of attention for postural responses required for stepping and resulting in freezing. Also, the non-freezing group may have prioritized accuracy over time as a compensatory strategy that may be slowing their gait but prevents freezing.